Fundamentals of technical mathematics with calculus - Kramer, Arthur D. (New York : McGraw Hill Education, 1984)
Fundamentals of Technical Mathematics with Calculus is designed for students who are preparing for technical or scientific careers. While it is desirable to have some background in elementary algebra, it is not essential. Chapter 2 is a thorough treatment of elementary algebra that can be used as a review or as an introduction. The text covers those areas of mathematics necessary for the beginning student up to and including the calculus-level student. The approach of this text stresses a working knowledge of mathematics and an application of mathematical ideas to technical and practical areas.
Chapter1. Arithmetic and the hand-held calculator -- Chapter2. Fundamentals of algebra -- Chapter3. Measurement: basic geometry and trigonometry -- Chapter4. Linear system and determinants -- Chapter5. Ratio, proportion and variation -- Chapter6. Factoring, fractions and the quadratic equation -- Chapter7. Exponents and radicals -- Chapter8. Trigonometry -- Chapter9. Trigonometric graphs -- Chapter10. Exponential and logarithmic functions -- Chapter11. Complex numbers -- Chapter12.Analytic geometry and quadratic system -- Chapter13. Polynomial functions and higher-degree equations -- Chapter14. Series and the binomial formula -- Chapter15. Trigonometric Identities and equations -- Chapter16. Inequalities and introduction to linear programming -- Chapter17. Introduction to computers and basic -- Chapter18. Limit and derivatives -- Chapter19. Application of the derivative -- Chapter20. The integral and its application -- Chapter 21. Transcendental functions -- Chapter22. Methods of integers -- Chapter23. Infinite series -- Chapter24. Introduction to differential equations.
Includes index.
Keywords: MATHEMATICS